Company Profile Pada Kantor Desa Lumpatan 1 Berbasis Web - Nopita Lestari; Zaid Romegar Mair; Ali Subhan Afrizal (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
The Lumpatan 1 Village Office which is located on Jl.Betung-Sekayu, Lumpatan, Sekayu, Musi Banyuasin Regency is the Lumpatan I Village Office for the Musi Banyuasin Regency, South Sumatra Province. This office has a duty as community service for the Musi Banyuasin area. However, this office does not yet have electronic media to convey information to the public, so it is difficult for people to find information about the office. So far, to find information about this office, people still come to the office directly without any media connecting the community with this office. In this study the method used is the Waterfall method which consists of five stages, namely: Needs Analysis, System Design, Coding, Testing or Implementation, and Maintenance. With this Company Profile, it will be useful for the Lumpatan 1 Village Office and users (Community) because it is a medium of information or a liaison between the office and the community. This Company Profile was built using the PHP and MySQL programming languages ​​as a medium for delivering data and the web server is localhost PHP Myadmin.